RANCANG BANGUN ALAT UJI GETARAN BEBAS SINGLE DEGREE OF FREEDOM HORIZONTAL BENDING BAR - Muhammad Aryasatya (2024)
Vibration is a subdiscipline of dynamics, which is the study of the repetitive motion of objects relative to stationary frames of reference or nominal positions. The process of learning vibration science in universities can take place through practicum activities. Single Degree of Freedom Horizontal Bending Bar Free Vibration Test Equipment is a tool that can be absorbed by the eyes and ears with the aim of helping educators make the learning process more effective and efficient. In finding Natural Frequencies, you can use the Rayleigh Method, Ansys Software 2022 R2 Student and Experiments. By comparing the Rayleigh method with Ansys 2022 R2 Student software, the natural frequency value with Copper, Brass and Stainless Steel material bars decreased by 3.489%, 9.571% and 1.797%. While comparing Rayleigh's method with experiments has varied results for lengths of 100 cm, 90 cm and 80 cm.